Atmospheric Corrosion Assessment of Structural Steel Exposed in The Environment of Palm Oil Processing (PKS) Industry Around Coastal Zone. Issue 1 (June 2019) - Zulfri, M; Ali, N; Husaini,; Fonna, S; Huzni, S; Mulyati, S; Cut, B
Abstract: Corrosion is the main cause of mature failures for infrastructure such as residential, public facilities, and also industries. Regarding of industry which having a rapid growth in the province of Aceh, especially Palm Oil Processing (PKS), the existence must be noticed in line with the environmental impact that caused by operations such as industrial gases which can be polluted the atmosphere. This condition can transform the infrastructure especially steel which is located around PKS becomes more vulnerable to the corrosion attacks. This study aims to investigate the corrosion atmospheric of structural steel in the PKS area and operational impacts for the infrastructure of PKS at PT. Ensem Sawita and PKS PT Anugerah Fajar Rejeki(AFR). Infrastructure corrosion is focused on measuring atmospheric corrosion rate of structural steel surrounding PKS area. Several types of steels will be selected as a specimen. The corrosion rate is calculated with mass-loss method referring to ASTM G50 standard. The location of selected PKS is around ± 5kmfrom the coast. The results are obtained after exposure during 4 months, the corrosion rate that occurs for 5 types of structural steel was in normal level. It is classified in the outstanding level of relative corrosion resistance (<1mpy). So, the usage of 5 types structural steel is relatively safe on palm industries and related areas.